Field Observations of Burial Mounds from the Soviet Military Topographic Maps for the Yambol Province, SE Bulgaria - Adela Sobotkova; Todor Valchev (Journal of Open Archaeology Data)
Burial mounds are a ubiquitous feature of the Bulgarian landscape, estimated at some 20,000 today [1]. One of the largest non-destructive efforts to document the outstanding mounded landscapes in the Yambol Province in Bulgaria (3,355 sq km) has been undertaken by the Tundzha Regional Archaeological Project (TRAP) as part of its mission to document the long-term history of human activity in the Middle Tundzha River [2–6]. TRAP has digitized near thousand potential mound symbols from the Soviet topographic maps covering the Yambol Province and then visited and systematically described their locations between 2009–2022, producing a dataset of 1260 feature observations of which 1095 were classified as mound observations. Each record lists the geographic coordinates, placename, land use, dimensions, conservation and archaeological potential of each feature. Mound chronology was added where known on the basis of excavation reports. The data have been used for studies of location preferences, cultural heritage decline, machine-learning training data and other methodological studies [7–10]. To facilitate further reuse of this data, the dataset has been aggregated, streamlined, and deposited on Zenodo.